(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2017)
Glycogen synthase kinase-3β (GSK-3β) is an important class of therapeutic drug target currently receiving wide attention. In our computational approach, shape-based similarity search was used to screen the SPECS database, based on the shape of Tideglusib molecule; a known GSK-3β inhibitor. The resulting virtual hits were applied for docking studies on the known binding pockets of GSK-3β. A novel compound [7,10-dioxo-4,5-dihydro-7H,10H-pyrano[3,2,1-ij]quinolin-8-yl acetate] proposed from docking results in the substrate site of GSK-3β was found to have inhibitory activity (IC50) above 100μM concentration in ADP-GloTM Kinase assay. This communication aims to put forward in identifying newer hit on GSK-3β target via virtual screening approach.